2018
DOI: 10.14507/epaa.26.2888
|View full text |Cite
|
Sign up to set email alerts
|

Voices from student teachers in New York: The persistence of a subtractive experience of the edTPA as a licensure exam for initial certification

Abstract: This article explores how candidates’ experiences in multiple initial certification programs within a single School of Education evolved over the first three semesters of New York’s implementation of edTPA as a requirement for initial licensure. The data reviewed included primarily surveys and interviews of teaching candidates, framed by critical perspectives on accountability, teacher performativity, and constructivist theories on learning to teach. Results suggest candidates’ perceptions of program alignment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…In these programs, the edTPA is placed at the intersection of what PSTs have learned in their preparation courses and their takeaways from the classrooms where they practice teaching. Consequently, tensions arise when the instructional visions of the performance assessment, the TEP, and the school context differ (Ahmed, 2019; Clayton, 2018; Meuwissen & Choppin, 2015). The detailed expectations of the edTPA can also feel unrealistic, which may constrain PSTs’ learning.…”
Section: The Edtpa and Psts’ Learning—overview Of The Literaturementioning
confidence: 99%
“…In these programs, the edTPA is placed at the intersection of what PSTs have learned in their preparation courses and their takeaways from the classrooms where they practice teaching. Consequently, tensions arise when the instructional visions of the performance assessment, the TEP, and the school context differ (Ahmed, 2019; Clayton, 2018; Meuwissen & Choppin, 2015). The detailed expectations of the edTPA can also feel unrealistic, which may constrain PSTs’ learning.…”
Section: The Edtpa and Psts’ Learning—overview Of The Literaturementioning
confidence: 99%
“…However, others found that reflective gains were tempered by the edPTA’s cumbersome logistical demands (Margolis and Doring, 2013). Indeed, mentor misunderstandings and the time-consuming nature of the edTPA can be subtractive forces in the student teaching experience (Clayton, 2018), which may be particularly problematic for candidates of color who already face a myriad of barriers to the profession (Petchauer et al., 2018). Furthermore, the developmental and educative gains that the edTPA may produce can be undercut by candidate context – specifically, their cooperating teachers’ understanding of the assessment’s requirements and their capacity to support (Kissau et al., 2019) – and the capacities of a candidates’ organizational context to comply with policy demands (De Voto, 2019).…”
Section: Accountability and Standardization In Teacher Educationmentioning
confidence: 99%
“…So, it was really hard to spend three days on one task, which is what you have to do for the edTPA.Other researchers have noted the tensions between the edTPA and the student teaching context (e.g. Clayton, 2018; Meuwissen and Choppin, 2015), and Emily’s experience further illuminated these complexities. However, a more critical analysis of Emily’s story speaks to the capacity of the edTPA to act as one more iteration of policy technologies enacting power over teachers.…”
Section: The Intersection Of Teacher Development and Policy: The Casementioning
confidence: 99%
“…The parameters of teacher education are influenced and controlled by policy makers and the structural mandates are legislated regulations for ITE (Kosnik et al, 2017, p. 138). In Australia, it appears that the drive to implement TPAs is an example of policy borrowing (Steiner-Khamsi, 2016), with little regard given to the critiques associated with the implementation of its counterpart the edTPA in the USA (Clayton, 2018;Cronenberg et al, 2016;Dover and Schultz, 2016;Greenblatt, 2018). Phillips and Ochs (2003) suggest that there are four stages of policy borrowing involving: cross-national attraction, a decision, implementation and internalisation.…”
Section: Teacher Quality and The Policy Problem Of Teacher Educationmentioning
confidence: 99%
“…Olson and Rao's (2017) research has found that considerable time and energy has been spent in ITE organisations on redeveloping programmes and courses to best align with edTPA. There is "edTPA driven instruction" (Kleyn et al, 2015, p. 96), with assessment driving PST engagement in teaching units (Clayton, 2018). Curriculum design is increasingly shaped to facilitate the ease of edTPA execution (Donovan and Cannon, 2018), and reportedly, there are "fewer conversations about teaching" beyond a focus on edTPA assessment (Cronenberg et al, 2016, p. 129).…”
Section: Pedagogical and Curriculum Implicationsmentioning
confidence: 99%